ANALISIS KASUS KORUPSI REKTOR UNIVERSITAS LAMPUNG DITINJAU DARI PERSPEKTIF KONSEP KORUPSI - Khumairo Qotrunnada; Michael Morgen Tarigan; Sellina Mutiara Anggodo (Kultura: Jurnal Ilmu Hukum, Sosial, dan Humaniora, 2023)
This writing aims to conduct an analysis of legal aspects involving corruption cases in new student admissions at the University of Lampung (UNILA). The main focus of the research is reviewing the sentence of 10 years in prison with evidence of around IDR 4.4 billion given to the former Chancellor of Unila, Karomani, in the context of this case. This writing will explain the verdict proposed by the panel of judges and the demands submitted by the Public Prosecutor (JPU) of the Corruption Eradication Commission (KPK). The research method was carried out qualitatively by collecting and analyzing data through literature study. The results of the discussion show that the corruption case of the Chancellor of the University of Lampung has complex root causes and involves various actors involved in the university's financial management system. This act of corruption indicates that the selection of new students is prone to corrupt practices. The reason is that the independent selection route has so far been considered closed, unmeasurable and not transparent. There are several causes of corruption cases at UNILA, such as: The number of registrations exceeding the available quota, a very long time span between exams and announcements, and limited infrastructure. Apart from the legal aspects, this article will also discuss the impact and impact of this case on the integrity and reputation of universities.